From Brain to Insomnia: Can Neurotrophic Factors Unlock the Sleep Puzzle After Stroke? [Letter] - Yang S; Pan H; Hong P (Nature and Science of Sleep, 2025)
Suqiong Yang, Hongrun Pan, Peikun Hong Department of Psychiatry, The Third Hospital of Jinjiang, Quanzhou, Fujian, 362000, People’s Republic of ChinaCorrespondence: Peikun Hong, Department of Psychiatry, The Third Hospital of Jinjiang, Quanzhou, Fujian, 362000, People’s Republic of China, Email jjsyedu2023@126.com